The Better Bathroom: A Spiritual and Political Landscape - Sattenhwaite, Andrew (UnderCurrents: Journal of Critical Environmental Studies, 1991)
Imagine this scene: luxuriant broadleaf greenery, ferns and verdant mosses. Perhaps a rock or two poking through. A pool, perhaps with clear water, but obviously deep, and a waterfall, flashing and tumbling, soothing to the ear, and lending the air a tangible humidity. Filtered sunlight dapples the waters.